1975
DOI: 10.1093/oxfordjournals.aje.a112122
|View full text |Cite
|
Sign up to set email alerts
|

Spherulin and Coccidioidin: Cross-Reactions in Dermal Sensitivity to Histoplasmin and Paracoccidioidin

Abstract: Until recently coccidioidin has been the only antigenic preparation available for detecting delayed dermal sensitivity induced by an experience with Coccidioides immitis. It is prepared from autolysates of the mycelial phase (saprophytic) of the fungus. A more sensitive reagent, spherulin, was developed in 1969 from the spherule phase (parasitic) of the organism. Use of spherulin showed that coccidioidin failed to detect approximately 30% of individuals specifically sensitive to C. immitis. However the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The explanation for this is not readily apparent. Coccidioidin skin tests are said to be largely specific for infection by that organism; some cross‐reactivity occurs because of infections by Blastomyces dermatiditis and Histoplasma capsulatum 11, 13, 14, 16–20 . While disease due to Blastomyces dermatiditis and Histoplasma capsulatum is more common in North Carolina than that due to Coccidioides immitis , 12, 13, 15, 17, 21–28 the prevalence in this study of positive skin tests was lower for the former organisms than for coccidioidin itself.…”
Section: Discussionmentioning
confidence: 55%
“…The explanation for this is not readily apparent. Coccidioidin skin tests are said to be largely specific for infection by that organism; some cross‐reactivity occurs because of infections by Blastomyces dermatiditis and Histoplasma capsulatum 11, 13, 14, 16–20 . While disease due to Blastomyces dermatiditis and Histoplasma capsulatum is more common in North Carolina than that due to Coccidioides immitis , 12, 13, 15, 17, 21–28 the prevalence in this study of positive skin tests was lower for the former organisms than for coccidioidin itself.…”
Section: Discussionmentioning
confidence: 55%
“…At the highest antibody concentration (Ig diluted 1:2, Fig. la), several precipitates were weak and barely discernible (Ags 12,13,14,22,24). These were not detectable at lower antibody concentrations.…”
Section: Resultsmentioning
confidence: 94%
“…Spherulin, which has become available more recently than coccidioidin, has not resolved this problem. Levine et al (20,22) reported spherulin more sensitive but no more specific than coccidioidin as reagents for intradermal tests. Huppert et al (15) found both reagents equally sensitive in serological tests, but spherulin was significantly less specific than coccidioidin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…David became interested in the cellular immune responses to Coccidioides and began working with Hillie in the field trials of a new skin-testing antigen, spherulin. 27,[36][37][38][39] As part of his other interests, Dr. Levine also tested antifungal drugs for pharmaceutical firms because his lab was well versed in the murine model of coccidioidal infection. One of the drugs tested by Dr. Levine was miconazole, sent to him by Janssen Pharmaceutical Company.…”
Section: Miconazole As An Alternative Treatment To Amphotericin Bmentioning
confidence: 99%